Solar Energy powered active Greenhouse for the cultivation of Fresh Food during winter in Trans Himalayan Cold Arid Region, India - Nazir, Sarfraz; Mustafa, Syed Basharat; Pandit, Anil; Norbu, Tsewang; Chaurasia, Om Prakash (Defence Life Science Journal, 2023)
The Trans-Himalayan Cold arid high altitude region of Ladakh have hostile climatic conditions particularly low temperature (-20°C to -45°C). The region shares international borders with two countries viz. China and Pakistan and hence large numbers of Army personnel are deployed in the region due to their strategic importance. Production of fresh food locally is difficult due to low atmospheric temperatures. The region remains cut off from the external world during the winter period for almost 6-8 months due to the closure of roads, which causes an acute shortage of fresh food. Some supply from other regions through the air is carried out but available only to a limited population and costly also, hence beyond the pocket of the common’s man. The inhabitants hence mostly have to survive on packaged food containing food preservatives and harmful chemicals, which are the causes of many diseases. In addition, the unavailability of fresh food causes nutritional deficiency in the inhabitants of the region. Production of fresh food locally seems possible and realistic in closed structures, only if the temperature is maintained. The objective of this study is to prove fresh food production by maintaining suitable temperatures in structures during peak winter using solar energy. Solar energy is available in plenty in the region and stood at 4 th position in India in terms of irradiation. A variety of fresh foods were produced by maintaining temperature in the coldest and largest existing structure using commercially available heating units successively from 2016-2019 during the winter period. The heating units were supplied energy from a Solar PV-based system. An average of 1500kgs-1800kgs of a variety of fresh vegetables were produced and supplied for the first time in the region during the peak winter period of 2016 to 2019. The survival percentage of 92.5% to 100% is found in a structure with an area of 3600 2 feet.Fresh foods were produced and supplied to the user by maintaining minimum survival temperature using solar energy as a source with commercially available heating technology in the largest and coldest existing structure.